The One Baptism and the Many Baptisms - Wilburn, Ralph Glenn (Theology today, 1965)
“We shall be able to work our way to an ecumenical resolution of our current differences on baptism only if we envisage our problem in historic perspective.” “…by tackling our problem in historic perspective I mean that certain modes and forms of baptism are particularly fitting for some historical situations, but not for others. History in part determines what forms are essential for the faith to possess genuine, cultural integrity. No one form of baptism is valid for all Christian people and for all ages.”